Odpowiedzi

2009-11-20T15:42:16+01:00
A) 2 * x = -28 /2
x = -14
spr. 2*-14=-28

b)-20 * x = 4 / -20
x = -⁴/₂₀
spr. : -20* -⁴/₂₀=4

c) x * -3 = -18 / -3
x= 6
spr. : 6*-3=-18

d) 64 / x = -16 /*x
64=-16x /-16
x=-4
spr. : -4*-16=64

e) -36 / x = -9 /*x
-36=-9x / -9
x=4
spr. : -9*4=-36

f) x / -3 = 45 /*-3
x=-105
spr. : -105/-3=45





2)
a)-8 / x = 4 /*x
-8=4x /4
x=-2

b)10 / x = -2 /*x
10=-2x / -2
x=-5

c) x / -25 = 4 / *-25
x=-100

d) -4 * x = -8 / -4
x=2

e) x * -12 = -36 /-12
x=3

f) x / -2 = -18 /*-2
x=36
Najlepsza Odpowiedź!
2009-11-20T16:54:51+01:00
2*x=-28 |:2
x=-14
spr.
-14*2=-28
-28=-28


-20*x=4 |:(-20)
x=4/-20
x=-1/5
spr.
-20*(-1/5)=4
20/5=4
4=4


x*-3=-18 |:(-3)
x=6
spr.
6*(-3)=-18
-18=-18


64/x=-16 |:64
x=-16/64
x=-1/4
spr.
64*(-1/4)=-16
-16=-16

-36/x=-9
x=4
spr:
-36/4=-9
-9=-9

x/-3=45|*(-3)
x=-135
spr.
-135/-3=45
45=45



-8/x=4 |:(-8)
x=-2

10/x=-2 |:10
x=-5

x/-25=-4|*(-25)
x=100


-4*x=-8|:-4
x=2

x*-12=-36|+12
x=-24

x/-2=-18 |*(-2)
x=36



2009-11-20T17:43:28+01:00
A) 2 * x = -28 /2
x = -14
spr. 2*-14=-28

b)-20 * x = 4 / (-20)
x = -⁴/₂₀
spr. : -20* -⁴/₂₀=4

c) x * -3 = -18 /(-3)
x= 6
spr. : 6*-3=-18

d) 64 / x = -16 /*x
64=-16x /-16
x=-4
spr. : -4*-16=64

e) -36 / x = -9 /*x
-36=-9x / -9
x=4
spr. : -9*4=-36

f) x / -3 = 45 /*-3
x=-105
spr. : -105/-3=45





2)
a)-8 / x = 4 /*x
-8=4x /4
x=-2

b)10 / x = -2 /*x
10=-2x / -2
x=-5

c) x / -25 = 4 / *-25
x=-100

d) -4 * x = -8 / -4
x=2

e) x * -12 = -36 /-12
x=3

f) x / -2 = -18 /*-2
x=36